Dystocia Due to Multiple Fetal Mummification of Quadruplet Kids in a Bidri Doe – A Case Report - Gond, Malasri; Bijurkar, Rajeshwar Gangaram; Doddagoudar, Venkangouda; Pasha, Mohd Mujaheed; Rathod, Yashoda (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Fetal mummification  occurs due to intrauterine aseptic death of the fetus with absorption of fetal fluids, which results in shriveled parchment like fetal membranes in papyraceous mummification or viscous chocolate colour of fetal membranes in haematic fetal mummification (Noakes et al., 2009). It is a rare obstetrical disorder in small ruminants compared to other domestic animals which is seen in the middle to last third of gestation (Roberts, 1971). In swine, dog and cat carrying large litter size there is uterine overcrowding of young ones with placental insufficiency (Long, 2009) whereas, in doe it is associated with Toxoplasmosis, Chlamydophila, Border disease and Coxiella burnetii infection (Edmondson et al., 2012). The present case report highlights on dystocia due to multiple fetal mummification and its management in a Bidri doe.